Project Team Bulding, Conflict and Negotiation - Dwi Ningsih, Arie; Ariani, Desy; Sagala, Suwastati; Harahap, Darmawati (Devotion : Journal of Research and Community Service, 2022)
The purpose of this study is to find out about conflict in negotiations. Organizational conflict is a difference of opinion or contradiction between two or more individuals or groups or work units in an organization because they have to share their limited resources in work activities, and the facts they have different goals, values, perceptions and interests. Internal conflict is often seen as a common event that is also faced by organizational leaders. Handling conflict requires a creative process that expects positive results, namely solutions and good relations between the two parties. Qualitative approach is a type of research that aims to analyze in depth a phenomenon related to the research focus to be explored. The sources used are primary and secondary data. Research results negotiation is a process in which two or more parties who have similar or contradictory interests meet and talk to reach an agreement. Conflict always arises when one person's point of view is different from that of others. In order for conflicts to provide optimal benefits and to reduce negative impacts, conflicts can be managed by preventing and handling conflicts so that the goals and objects of negotiation can be achieved. If there is no way in negotiations, it can be proposed to use delays to give time for both parties to think repeat and meditate according to the difficult situation. This delay does not mean postponing negotiations, but rather provides an opportunity when tensions escalate and this delay must be used by both parties and not used to avoid conflict.